Role of neuroimaging in first seizure diagnosis - Crocker, Candice E.; Pohlmann-Eden, Bernd; Schmidt, Matthias H. (Seizure, 2017)
The primary goal of neuroimaging in a first, unprovoked seizure is to identify a lesion that can explain the seizure. Secondarily, neuroimaging may be used to predict seizure recurrence and assist with the diagnosis of epilepsy. However, the events leading from a first seizure to epilepsy, with or without an identifiable epileptogenic lesion, are not well understood, and it is not always clear which lesions are epileptogenic as opposed to incidental. Much neuroimaging research to date has focused on findings in chronic epilepsy, rather than first seizure. Dedicated epilepsy imaging with high quality MRI protocols maximizes the likelihood of a diagnosis. However, a significant proportion of patients are MRI-negative, prompting researchers in the field to continue the search for better imaging strategies. Here we describe the role of neuroimaging in the assessment of a first seizure, the current state of the art and possible future directions.